Necrotizing fasciitis: diagnostic and prognostic value of laboratory risk indicator for necrotizing fasciitis score - Soitkar, Angir; Akhtar, Murtaza; Choudhari, Abhay; Deshmukh, Satish (International Surgery Journal, 2019)
Background: Necrotizing fasciitis (NF) is a potentially life threatening disease. Delayed recognition and surgical intervention is directly linked to increased mortality. Laboratory risk indicator for necrotizing fasciitis (LRINEC) score, a laboratory oriented tool has potential to prevent morbidity and mortality but there exhibits a controversy regarding its utility which needs re-evaluation to prove it’s utility. Methods: A tertiary care hospital based observational study aims to evaluate diagnostic and prognostic value of LRINEC score. Patient above 18 years clinically diagnosed as SSTI and confirmed as NF histopathologically without co-morbidities were enrolled as subjects. Clinical evaluation and laboratory oriented LRINEC score were the study factors. Outcome factors were morbidity and mortality and histopathological confirmation of NF. Patients were analyzed as cellulitis and NF with identification of factors associated with NF; Univariate analysis with Kaplan-Meier survival analysis and ROC plotting was done. Results: Total 166 patients were enrolled with mean age of 47.14±15.76 years and 2:1 is the male : female ratio and. A total of 117 patients were diagnosed as Cellulitis and 49 patients were NF. Clinically Discharge, fever and cuticular necrosis was statistically associated with NF (p<0.01). Mortality in NF was 22.4% and no mortality in Cellulitis. Mean LRINEC score in cellulitis and NF was 1.95±0.972 and 7.57±1.51 (p<0.01). Survival analysis graph and ROC showed LRINEC score of 6 as diagnostic and score ≥9 as poor prognostic indicator. Conclusions: LRINEC score is a useful diagnostic and prognostic tool in patients of NF.